Upaya Memiskinkan Koruptor sebagai Sanksi Alternatif bagi Pelaku Korupsi Perspektif Pidana Umum dan Pidana Islam - Ishomuddin, Ianatullah (Journal of Comprehensive Islamic Studies, 2023)
The increasing escalation of corruption over time has become a serious concern for legal experts to think about the type of punishment that could have a deterrent effect. This article discusses an alternative solution to resolve the problem of increasingly rampant corruption. The main idea offered is an effort to impoverish corruptors by implementing appropriate, appropriate and maximum punishment. The problem that is the focus is how can efforts to impoverish corruptors become an appropriate alternative punishment for perpetrators of criminal acts of corruption? This article comes from qualitative research by conducting collaborative legal exploration based on general criminal law and Islamic criminal law. The research results show that there are three alternatives that can be applied to perpetrators of corruption, including; first prison sentence of 10-20 years; secondly, a fine of 1/2 of the value of the money corrupted or at least and a replacement of 100% of the money corrupted; and third, deprivation of rights, both in prison and outside prison. Eskalasi korupsi yang semakin lama semakin meningkat telah menjadi perhatian serius para ahli hukum untuk memikirkan jenis hukuman yang bisa membawa efek jera. Artikel ini membahas sebuah alternatif solusi bagi penyelesaian masalah korupsi yang kian merajalela. Gagasan utama yang ditawarkan adalah upaya memiskinkan koruptor dengan penerapan hukuman yang tepat, setimpal dan maksimal. Permasalahan yang menjadi fokus adalah bagaimana upaya pemiskinan koruptor dapat menjadi alternatif hukuman yang tepat bagi pelaku tindak pidana korupsi? Artikel ini berasal dari penelitian kualitatif dengan melakukan penggalian hukum secara kolaboratif berdasarkan hukum pidana umum dan hukum pidana Islam. Hasil penelitian menunjukkan bahwa ada tiga alternatif yang dapat diterapkan untuk para pelaku tindak korupsi, antara lain; pertama hukuman penjara 10-20 tahun; kedua denda sebesar 1/2 dari nilai uang yang dikorupsi atau minimal serta pengganti sebesar 100% dari uang yang dikorupsi; dan ketiga, pencabutan hak, baik hak yang ada di dalam penjara maupun di luar penjara.